2004
DOI: 10.1144/0016-764903-024
|View full text |Cite
|
Sign up to set email alerts
|

55 million years of continuous anatexis in Central Iberia: single-zircon dating of the Peña Negra Complex

Abstract: Single-zircon evaporation and ion-microprobe dating of migmatites and anatectic granites in the Peña Negra Complex of Central Iberia reveal that the Variscan anatexis occurred continuously from 352 to 297 Ma, with a maximum at 335–305 Ma. Anatexis began coeval with the main collision of continental masses. A limited melting event, probably related to syncollision crustal-scale shear zones, produced a population of zircons with ages of c . 350 Ma. The production of new zircons decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 16 publications
6
25
1
Order By: Relevance
“…7) suggest that the M 3 melting was rather long-lived (> 20 Ma), but did not result in the formation of large granitic bodies; melt remained confined to migmatites and was rarely extracted and transferred into true plutons. A similar pattern has been described in other segments of the Variscan belt, such as Central Spain (Montero et al 2004) or Calabria (Schenk 1990;Graessner et al 2000), suggesting that this process occurred throughout the whole Variscan belt. The M 3 and M 4 events, therefore, were very distinct.…”
Section: Long-lived Crustal Melting and Catastrophic Granite Productionsupporting
confidence: 82%
“…7) suggest that the M 3 melting was rather long-lived (> 20 Ma), but did not result in the formation of large granitic bodies; melt remained confined to migmatites and was rarely extracted and transferred into true plutons. A similar pattern has been described in other segments of the Variscan belt, such as Central Spain (Montero et al 2004) or Calabria (Schenk 1990;Graessner et al 2000), suggesting that this process occurred throughout the whole Variscan belt. The M 3 and M 4 events, therefore, were very distinct.…”
Section: Long-lived Crustal Melting and Catastrophic Granite Productionsupporting
confidence: 82%
“…Cordierite leucogranites gave Rb-Sr ages in the range of 305 to 295 Ma. These data are in disagreement with the 321 Ma obtained by [20] for new zircons crystallizing from the granitic melt. Our younger age coincides with the age that these authors obtained for the end of the anatexis at Peña Negra.…”
Section: The Rockscontrasting
confidence: 87%
“…The granodiorites gave a Rb-Sr age of 310 Ma [18,22]. This age coincides with the 309 Ma zircon age obtained by [20]. Granodiorites represent the most important anatectic product of the migmatites, with respect to volume, and their age also dates the most intense period of partial melting of the Complex.…”
Section: The Rockssupporting
confidence: 63%
See 1 more Smart Citation
“…(Petitgirard et al, 2009), and sustained continuous anatexis for tens of m.y. (Montero et al, 2004). Also, Gordon et al (2009) suggested that the Valhalla migmatite complex in Canada maintained an elevated temperature, sufficient for an open U-Pb system in monazite, in excess of 7 m.y.…”
Section: Discussionmentioning
confidence: 99%